Blockchain and IoT for Transparent Carbon Tracking and Emission Reduction in Global Supply Chains - Jessica Obianuju Ojadi; Olumide Akindele Owulade; Chinekwu Somtochukwu Odionu; Ekene Cynthia Onukwulu (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The increasing urgency of climate change mitigation necessitates transparent and efficient carbon tracking mechanisms within global supply chains. Blockchain and the Internet of Things (IoT) present a synergistic approach to enhancing traceability, accountability, and automation in carbon emissions monitoring and reduction. Blockchain’s decentralized and immutable ledger ensures data integrity, preventing fraud and manipulation, while IoT sensors provide real-time data collection on emissions, energy consumption, and supply chain activities. By integrating these technologies, organizations can achieve end-to-end visibility, ensuring compliance with environmental regulations and corporate sustainability goals. This paper explores the application of Blockchain and IoT in transparent carbon tracking and emission reduction across global supply chains. The study examines how blockchain’s smart contracts enable automated verification of carbon credits and emissions data while ensuring secure and tamper-proof recordkeeping. IoT devices, including smart meters and carbon sensors, facilitate real-time emissions monitoring, allowing stakeholders to track and optimize energy usage. The combination of these technologies enhances supply chain transparency by enabling all participants, including manufacturers, logistics providers, and regulatory bodies, to access verifiable and auditable carbon data. Furthermore, the paper discusses the role of decentralized consensus mechanisms in validating emission records and preventing data manipulation. Blockchain-powered carbon trading platforms incentivize sustainable practices by enabling efficient carbon credit transactions. The integration of IoT and blockchain also fosters improved data interoperability, allowing seamless communication between diverse systems across different industries and regions. Challenges such as data privacy concerns, scalability limitations, and the high energy consumption of blockchain networks are examined, alongside potential solutions such as layer-2 scaling techniques and energy-efficient consensus protocols like Proof-of-Stake (PoS). The study concludes by presenting future research directions, emphasizing the need for standardized regulatory frameworks, enhanced interoperability solutions, and AI-driven analytics to optimize emissions management. By leveraging Blockchain and IoT, global supply chains can achieve greater transparency, efficiency, and sustainability, ultimately contributing to carbon footprint reduction and compliance with international climate policies. This paper provides a comprehensive analysis of the transformative potential of these technologies in driving environmentally responsible supply chain operations.